Revised Draft Second Five Year Plan Assam as Provisionally Approved by the Planning Commission Part I (General Appreciation and Summary) Government of Assam - Planning Commission (Planning Commission, 1955)
In response to Planning Commission’s instructions received from time to time, the first Draft of the Second Five Year Plan for Assam was prepared in August 1955 both for presentation to the Planning Commission and for inviting public opinion thereon. The first Draft which was printed and given wide circulation, envisaged an outlay of Rs. 290.7 crores, provided for an employment potential of 2.6 lakhs and an increase in the State national income of 22 per cent and a target of State per capita income of Rs. 308 against the national target of Rs. 344 visualised at the end of Second Five Year Plan in the Draft National Plan Frame.
Department of Planning and Development, Government of Assam